Macro and Micronutrient Intake and Its Effects on Hemoglobin Levels and Breast Milk Quality in Breastfeeding Mothers - Rukmaini; Bella Rachmasari; Lisa Trina Arlym (Global Medical & Health Communication (GMHC), 2025)
Anemia during the postpartum period can cause complications that affect maternal recovery and the quality of breast milk. Adequate intake of macro- (carbohydrates, proteins, fats) and micronutrients (vitamins, minerals) is essential to maintain hemoglobin (Hb) levels and ensure optimal breast milk composition. This study aimed to analyze the influence of macro- and micronutrient intake on Hb levels and breast milk quality among postpartum mothers in Palmerah District, West Jakarta. This study used a cross-sectional design involving 30 postpartum mothers as respondents, selected through total sampling. The research was conducted in Palmerah District, West Jakarta, from December 2024 to January 2025. Data were collected using a 3×24-hour food recall, analyzed with Nutrisurvey 2007, and laboratory tests to measure Hb levels and breast milk protein content. The observed variables were macronutrient intake (carbohydrates, proteins, fats), micronutrient intake (iron, vitamins, minerals), Hb levels, and breast milk protein. Data were analyzed using descriptive statistics for univariate analysis, Pearson correlation for bivariate analysis, and simple linear regression for multivariate analysis. A significant positive correlation was found between iron intake and Hb levels (r=0.622, p<0.05), accounting for 38.6% of the variation in Hb levels. Iron intake was also significantly associated with the protein content of breast milk (r=0.580, p=0.001). In contrast, protein, carbohydrate, and fat intake showed no significant relationship with Hb levels or breast milk protein. In conclusion, iron intake plays a vital role in improving Hb levels and breast milk quality among postpartum mothers in Palmerah District, West Jakarta. Strengthening nutritional programs that promote sufficient iron consumption is essential to support maternal health and ensure optimal infant nutrition.